SPORT SPECIFIC PREVALENCE OF CHONDRAL INJURIES IN THE HIP. Issue 4 (1st February 2017) - Briggs, Karen; Philippon, Marc; Trinidade, Christiano; Daniela, Maglione
Abstract : Background: Cartilage defect in the hip can progress to osteoarthritis. It is unclear if certain sports put an individual at increased risk of cartilage injury. Objective: The purpose of this study was to determine the prevalence of chondral defects in the an active population of recreational and elite athletes that underwent hip arthroscopy for femoroacetabular impingment (FAI). Design: Comparative cohort. Setting: Clinical recreational to elite athletes. Patients (or Participants): 1037 (769 recreational/amateur and 268 professional athletes)patients between 18 to 50 years old. The exclusion criteria included joint space of 2 mm or less, patients over the age of 50 and nonactive individuals. Interventions (or Assessment of Risk Factors): Independent variable was presence of cartilage damage in the hip. Main Outcome Measurements: Type of Sports: Rotational sports; Repetitive non weightbearing; Running sports; Snow sports; Soccer; Football; Hockey; Dance. Results: Chondral defects were seen in 822 of 1037 hips. In professional athletes, 86% had a chondral defect and in recreational 77% had a chondral defect (p=0.002). Grade III/IV defects were seen in 476 of 1037 hips. In professional athletes, 50% had grade III/IV defects and 45% in recreational athletes (p=0.155).The prevalence of chondral defects was different by sport for both amateur (p=<0.001) and professional athletes (p=0.001). Grade 3 or 4 defects in professionals were most commonly see in soccer, football and hockey. Grade 3 or 4 defects in recreational/amateur athletes were most commonly seen in football, hockey and skiing. Significant differences between pro and recreational athletes was seen in hockey, rotational sports and running. Conclusions: Prevalence was different between sports and level of athletes. Sports involving contact, such as football, soccer, hockey, had higher risk of more severe defects (grade III / IV), as was snow sports with falls at high speed and sports involving repetitive rotation movements leading to high forces crossing the joint.